STRATEGI PENGEMBANGAN PRODUK AGROINDUSTRI PADA AREA BELANJA Di AGROWISATA CAU CHOCOLATE FACTORY - Trisnayanti, Ni Made; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Agrotourism is a tourist activity that involves the use of agricultural land or related facilities that attract tourists. The increasing number of agrotourism will have implications for the level of competition that is increasingly high among agrotourism. The high competition is one of the factors to carry out product development strategies. The objectives purpose of this study are: 1) to find out the types of agroindustry products sold in the shopping area in agrotourism, 2) determine which agroindustry products are most popular with tourists in the shopping area, 3) to formulate alternative strategies and set priorities for agroindustry product development strategies. This research was conducted at Cau Chocolate Factory Agrotourism. This study uses the SWOT method to determine the alternative strategies used, and TOPSIS to rank these alternatives. The strategy that can be applied in Cau Chocolate Factory Agrotourism is a intensive strategy, the priority of the chosen strategy is 1) expanding the marketing of chocolate products, 2) promoting processed chocolate products to social media, 3) strengthening cooperation with suppliers and between tourism actors and similar companies. Keywords: Agrotourism, Agroindustry, SWOT, TOPSIS, Chocolate Factory